2014
DOI: 10.4314/bcse.v28i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Lead accumulation in the roadside soils from heavy density motor way towns of eastern Ethiopia

Abstract: ABSTRACT. The levels of lead pollution in the roadside soils of the heavy density motor ways of Eastern Ethiopia, in particular; Modjo, Bishoftu and Adama towns were studied. Soil samples were collected from a total of 22 sampling sites while the control samples were obtained from places about 1 km away from the main roads of each town. Concentrations of lead, in soil samples, were determined using flame atomic absorption spectrometer and the average concentrations of lead were found to be 93.3 ± 1.0, 79.4 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Scholars conclude that highway environments are highly polluted due to emission from vehicles, and they confirmed that soil, water, and air around busy roads have significantly higher lead content than nonbusy roads [10]. This claim is supported by other researches indicating that vehicular emission is responsible for more than 90 percent of all atmospheric emission and roadside soil lead content [11]. There is also a strong positive and direct relationship between roadside soil lead and traffic density of the road [12].…”
Section: Resultsmentioning
confidence: 79%
“…Scholars conclude that highway environments are highly polluted due to emission from vehicles, and they confirmed that soil, water, and air around busy roads have significantly higher lead content than nonbusy roads [10]. This claim is supported by other researches indicating that vehicular emission is responsible for more than 90 percent of all atmospheric emission and roadside soil lead content [11]. There is also a strong positive and direct relationship between roadside soil lead and traffic density of the road [12].…”
Section: Resultsmentioning
confidence: 79%
“…High lead levels have been reported in soils and vegetables grown close to the major roads of Dar es Salaam, Tanzania, [37] and Ethiopia [38]. This very low level of lead is generally very safe and cannot lead to any health hazard for consumers.…”
Section: Heavy Metal Contentmentioning
confidence: 99%
“…High lead levels have been reported in soils close to the major roads of Dar es Salaam, Tanzania, [46] and in other countries e.g. Ethiopia [48]. However, this level of lead is generally safe and cannot lead to any health hazard for consumers.…”
Section: Heavy Metal Contentmentioning
confidence: 99%